A Proposal to Address NFL Club Doctors' Conflicts of Interest and to Promote Player Trust. (November 2016) - Cohen, I. Glenn; Lynch, Holly Fernandez; Deubert, Christopher R.
Abstract : How can we ensure that players in the National Football League receive excellent health care they can trust from providers who are as free from conflicts of interest as realistically possible? NFL players typically receive care from the club's own medical staff. Club doctors are clearly important stakeholders in player health. They diagnose and treat players for a variety of ailments, physical and mental, while making recommendations to the player concerning those ailments. At the same time, club doctors have obligations to the club, namely to inform and advise clubs about the health status of players. While players and clubs share an interest in player health—both of them want players to be healthy so they can play at peak performance—there are several areas where their interests can diverge, and the divergence presents legal and ethical challenges. The current structure forces club doctors to have obligations to two parties—the club and the player—and to make difficult judgments about when one party's interests must yield to another's. None of the three parties involved should prefer this conflicted approach. We propose to resolve the problem of dual loyalty by largely severing the club doctor's ties with the club and refashioning that role into one of singular loyalty to the player‐patient. The main idea is to separate the roles of serving the player and serving the club and replace them with two distinct sets of medical professionals: the Players' Medical Staff (with exclusive loyalty to the player) and the Club Evaluation Doctor (with exclusive loyalty to the club). We begin by explaining the broad ethical principles that guide us and that help shape our recommendation. We then provide a description of the role of the club doctor in the current system. After explaining the concern about the current NFL player health care structure, we provide a recommendation for improving this structure. We then discuss how the club medical staff fits into the broader microenvironment affecting player health.